Study on the Influence of Water Immersion in Loess Stratum on the Bearing Capacity of Foundation Bearing Layer of Pipe Gallery. (16th May 2022) - Pan, Xiaoting; Ma, Huabing; Zhou, Haicheng; Zhu, Li; Shan, Hongwei
Abstract : Aiming at the influence of water immersion in the loess stratum on the bearing capacity of the pipe gallery foundation, taking the prefabricated pipe gallery demonstration project in Xiongan New District as the research object, the static penetration test and indoor triaxial test of the foundation bearing layer of the pipe gallery before and after water immersion were carried out. In the experiment, the loss law of loess foundation bearing capacity before and after water immersion was analyzed by using the obtained soil physical index changes. The research results show that the foundation bearing capacity calculated using the static penetration test data before and after immersion are in good agreement with the field plate load test results, and the eigenvalues of the foundation bearing capacity calculated using the shear strength index are higher than the field measured results. According to the results of the static penetration test, the bearing capacity of the foundation after immersion will decrease, but the reduction range is within 4%, and there is a certain loss; the bearing capacity of the foundation before and after immersion calculated according to the shear strength index is reduced by 2.5%. It shows that the bearing capacity of the foundation will be lost to a certain extent after immersion in water, but the loss is small. It is recommended to strengthen drainage measures in the later stage to prevent the foundation from being soaked by rainwater.